The role of anisotropic ring current ions in the excitation of lowfrequency waves during magnetic storms - Kakad, Amar; Singh, S.V.; Reddy, R.V.; Lakhina, G.S. (My University, 2006)
The compositional variations of H+ and O+ ions during the intense geomagnetic storms have considerable effects on ring current plasma dynamics. The storm time ring current is populated with energetic particles having anisotropic distribution functions that can provide free energy for the excitation of different types of plasma waves. A four component model has been developed to study the effect of thermal anisotropy of H+ and O+ ions on the excitation of low-frequency quasi-electrostatic waves. A dispersion relation is derived in the ring current plasma consisting of isotropic electrons, background cold protons, and energetic protons and oxygen ions, both having Dory-Guest-Harris (DGH) type loss cone distributions. The dispersion relation is solved numerically for storm time ring current parameters. These modes can scatter ring current ions into the atmospheric loss-cone leading to their precipitation into the ionosphere, thus, providing a ring current decay mechanism complementary to the charge exchange.
Keywords: Anisotropic ions; Low-frequency waves; Magnetic storms; Ring current.